System Design of Shrimp Fishery Water Supply from Solar Panel - Wardana W (Bandar Lampung University (UBL), 2017)
Keeping the state of water in shrimp ponds is very important because the shrimp are very sensitive to changes in their environment. Water conditions should remain good so that the shrimp can be convenient and fast pertumbuhanya. To supply water for shrimp farming requires a water pump to move the water from the inlet to the pond. Ir pumps are already on the market in general use fuel or electricity from PLN to pump function. New and renewable energy began to receive attention from the onset of the energy crisis the world is in the 70s and one of the energy is solar energy. Abundant sunlight and even for a tropical country, Irradiating the sun almost all years. Therefore solar power plant is suitable for application in Indonesia. Solar power has several advantages such as energy provided free of charge, Maintenance is easy and there are no moving parts so it does not make a sound / noise, as well as able to work automatically. But solar power also has disadvantages that the energy produced depends on the intensity of sunlight is not available 24 hours a day so we need a storage medium as a source of energy in the form of a battery when the light intensity decreases, or even none at all. The battery charging process is set with a battery charger